THE EFFECT OF PROFIT SHARING FINANCING, FIRM SIZE AND FINANCIAL PERFORMANCE OF ISLAMIC SOCIAL REPORTING (ISR) DISCLOSURE IN SHARIA GENERAL BANKS IN INDONESIA IN 2012-2018 - Astuti, Windi (Asosiasi Dosen Akuntansi Indonesia, 2020)
This study aims to analyse the effect of profit sharing financing, firm size and financial performance on Islamic Social Reporting (ISR) disclosure in Islamic commercial banks in Indonesia. This type of research in this research is causal comparative. The population of this study is the Islamic banks registered at the Financial Services Authority in 2012-2018. The sample selection method uses a census (saturated sample), so the number of samples used is 13 sample data. The data collection method used is documentation technique. Methods of data analysis using descriptive statistical methods, panel data regression analysis, and using Eviews software tools. The results showed that profit sharing financing had no significant positive effect on Islamic Social Reporting (ISR) Disclosure, firm size had a significant positive effect on Islamic Social Reporting (ISR) Disclosure, and financial performance had a significant negative effect on Islamic Social Reporting (ISR) Disclosure